2023
DOI: 10.3389/fgene.2023.1118273
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic markers of ferroptosis-related long non-coding RNA in lung adenocarcinomas

Abstract: Ferroptosis is a recently established type of iron-dependent programmed cell death. Growing studies have focused on the function of ferroptosis in cancers, including lung adenocarcinoma (LUAD). However, the factors involved in the regulation of ferroptosis-related genes are not fully understood. In this study, we collected data from lung adenocarcinoma datasets of the Cancer Genome Atlas (TCGA-LUAD). The expression profiles of 60 ferroptosis-related genes were screened, and two differentially expressed ferropt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 63 publications
0
2
0
Order By: Relevance
“…[21] Although ferroptosis was considered as the effective potential to overcome cancer progression, till now, the exact mechanism of ferroptosis in LUAD progression remains elusive. [22,23] In the present study, we downloaded the RNAseq data and clinical data of human LUAD from TCGA and Wilcoxon rank sum test was performed to selected the prognosis-related DEGs in LUAD patients. We also downloaded the ferroptosis-related datasets from GeneCards and the intersecting genes were selected, including ALG3, H2AX, VDAC1, RUVBL2, FKBP3, CISD2, TFAP2A and LDHA, all of which were involved in the ferroptosis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…[21] Although ferroptosis was considered as the effective potential to overcome cancer progression, till now, the exact mechanism of ferroptosis in LUAD progression remains elusive. [22,23] In the present study, we downloaded the RNAseq data and clinical data of human LUAD from TCGA and Wilcoxon rank sum test was performed to selected the prognosis-related DEGs in LUAD patients. We also downloaded the ferroptosis-related datasets from GeneCards and the intersecting genes were selected, including ALG3, H2AX, VDAC1, RUVBL2, FKBP3, CISD2, TFAP2A and LDHA, all of which were involved in the ferroptosis of cancer cells.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it is reported that LPS-stimulated mouse alveolar macrophages increased the expression of hepcidin mRNA and decreased transmembrane protein ferroportin (FPN) mRNA, leading to a reduction in iron efflux, and the results suggest that the lung hepcidin–FPN axis may correlate with iron homeostasis during alveolar macrophage injury induced by LPS [ 9 ]. Recently, long non-coding RNAs (lncRNAs) have been considered as important mediators of iron metabolism [ 10 ]. Through regulating the amount and function of iron, seven iron metabolism–related lncRNAs are recognized as an independent prognostic factor for the overall survival of lung adenocarcinoma patients.…”
Section: Introductionmentioning
confidence: 99%